SCLERAL WOUND HEALING IN PARS PLANA VITRECTOMY : A NARRATIVE REVIEW - Nabita Aulia; Habibah S. Muhiddin; Budu; Andi Muhammad Ichsan; Hasnah Eka (Majalah Oftalmologi Indonesia, 2023)
Background: Scleral wound healing involves cell death, migration, proliferation, differentiation, and ECM remodeling. Damaged connective tissue and blood arteries produce extravasation of blood cells, platelets, and plasma proteins when incisions are made in the conjunctiva and sclera (e.g. fibronectin, fibrinogen and plasminogen). Aims: This literature review aims to elaborate scleral wounds constructions in general, wound healing process, and closure of the scleral wound after pars plana vitrectomy. Methods: This literature review conducted 35 research publications from 2013-2022 who cited from some reputable sources using “wound healing”, “scleral”, “sutureless”, and “vitrectomy” as keywords. Results: The self-healing process that takes place after scleral wounds are closed. On the second day, fibrous tissue grows to fill in the wound gap, marking the beginning of the wound healing process. On the third day, the connective tissue was then expanded to span the entire thickness of the wound. On day five, the connective tissue begins to thicken and begins to align with the lamellae of the normal connective tissue that is around it. This process continues until day seven. On the seventh day, it looked that the wound had healed and normal tissue creation had taken place. Conclusion: Transconjunctival sutureless vitrectomy accelerated scleral wound healing. Small trocars and Zorro incisions speed scleral healing. Otherwise, silicone oil didn't affect scleral wound healing.